The teaching of semiology and semiotechnics from the perspective of nursing graduates after remote teaching (Research, Society and Development, 2022)
Identify the understanding and satisfaction of nursing undergraduates who are taking or have attended practical subjects, including semiology and semiotechnics remotely. Descriptive, exploratory, quantitative study, developed online after authorization from the research ethics committee. Sample composed of women (47.1%; n=32) between 18 and 29 years (44.1%) from the northeast region (54.4%; n=37), living with family members (57.4%; n= 39), income between one and three minimum wages (44.1%; n=30), working (38.2%; n=26) in technology (20.6%; n=14) in a private institution (61, 8%; n=42), in the morning (33.8%; n=23) fourth period (23.5%; n=16). Internet access (61.8%; n=42) with financing (41.6%; n=31) did not have another higher education course (55.9%; n=38) or technical course (33.8%; n =23). Although the institutions of these individuals have adhered to remote teaching of practical classes (55.9%; n=38), they attended semiology and semiotechnics classes in face-to-face format (33.8%; n=23). The highest averages of student satisfaction were present in the questions of “institution's physical infrastructure”, “classrooms” and “relationship with teachers”. In turn, the lowest averages were related to "Watching practical classes at home remotely in the semiology and semiotechnics subject", "switching from face-to-face teaching to remote teaching in practical subjects including semiology and semiotechnics" and "preparation to perform technical procedures of semiology and semiotechnics after remote classes”. It is concluded that a reconciliation between digital education and the training of professionals in the health area is necessary, and that nursing students prefer face-to-face practical classes in the discipline of semiology and semiotechnics.